2019
DOI: 10.31234/osf.io/6ztjx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Mind In Its Own Place: The Difficulties and Benefits of Thinking for Pleasure

Abstract: This chapter is concerned with a type of thinking that has received little attention, namely intentional “thinking for pleasure”—the case in which people deliberately focus solely on their thoughts with the goal of generating positive affect. We present a model that describes why it is difficult to enjoy one's thoughts, how it can be done successfully, and when there is value in doing so. We review 36 studies we have conducted on this topic with just over 10,000 participants. We found that thinking for pleasur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Boredom tasks varied across studies. Some used a thinking paradigm in which participants were asked to entertain themselves with their thoughts either alone in an unadorned room or in everyday life for 2–6 min (Westgate et al, 2017 Study 5; Westgate et al, 2017 Footnote 5; Wilson, Westgate, Buttrick, & Gilbert, 2017). In others participants completed a 5–10 min simulated air traffic control task (adapted from Markey et al, 2014) in which they identified whether two lines on a circular plot would eventually collide (Westgate et al, 2017, Study 2; Westgate, 2016a, 2016b, 2016c, 2016d, 2016e, 2016f, 2017a, 2017b, 2017c).…”
Section: Methodsmentioning
confidence: 99%
“…Boredom tasks varied across studies. Some used a thinking paradigm in which participants were asked to entertain themselves with their thoughts either alone in an unadorned room or in everyday life for 2–6 min (Westgate et al, 2017 Study 5; Westgate et al, 2017 Footnote 5; Wilson, Westgate, Buttrick, & Gilbert, 2017). In others participants completed a 5–10 min simulated air traffic control task (adapted from Markey et al, 2014) in which they identified whether two lines on a circular plot would eventually collide (Westgate et al, 2017, Study 2; Westgate, 2016a, 2016b, 2016c, 2016d, 2016e, 2016f, 2017a, 2017b, 2017c).…”
Section: Methodsmentioning
confidence: 99%
“…Cross‐sectional data suggests that individual differences in boredom (e.g., “I am seldom bored”) drop steadily from 18 through middle age, before largely plateauing around age 60; the limited longitudinal data available support this trend (Giambra, Camp, & Grodsky, 1992). Older Americans are slightly less likely to be bored on a day‐to‐day basis, compared to younger ones (Chin et al, 2017), and the same is true for directed activities in the lab, such as thinking for pleasure (Wilson, Westgate, Buttrick, & Gilbert, 2019). To the extent that older adults experience less boredom, it's likely due to age‐related changes in their ability to pay attention and find meaning.…”
Section: The Social Ecology Of Boredommentioning
confidence: 99%
“…Although speculative in our context, it is possible that students from the U.S.A. feel worse during an empty time interval than German students. This is a topic for further investigation, especially since current cross-cultural investigations, conducted in 11 countries, indicate that across cultures "thinking for pleasure" is judged as being significantly less enjoyable than being engaged in an external activity [7,23]. In our study, there were cross-cultural differences in judging the period of "just thinking", which were explainable through variations in individual differences.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, thinking as an enjoyable activity has recently been addressed in publications under the headline of "thinking for pleasure". Studies have shown that "thinking for pleasure" does not come easily, it may even be cognitively demanding, but can be enjoyable if conducted under the right conditions with simple cognitive aids that make it easier and more enjoyable for study participants [22,23]. In one of these studies [23], participants reported that the more they aimed to have pleasant thoughts, the more enjoyment the actually experienced.…”
Section: Discussionmentioning
confidence: 99%